SOSIALISASI PEMANFAATAN CANGKANG BIJI KARET MENJADI BIO BRIKET DI DESA GELEBAK, DALAM KABUPATEN BAYUASIN - Muhammad Yerizam; Cindi Ramayanti; Mustain Zamhari; Feri; Helen Chairunisa; Saqila Putri Aulia (Politeknik Negeri Sriwijaya, 2024)
Community Service Activities aim to increase public awareness about the benefits of rubber seed shells and their management. We target the villagers of Gelebak Dalam to equip them with the necessary skills in the management of rubber seed shell utilization. Through these activities, we identify the potential and dangers associated with rubber seed shells and provide practical training on biobriquette production. It is hoped that this initiative can increase the income of the local community and reduce the negative impact of rubber seed shell waste. The results of this service include yield reports, guidebooks, and scientific articles, which will empower residents to produce biobriquettes independently.